A METHOD FOR CALCULATION OF MORSE POTENTIAL FOR FCC, BCC, HCP CRYSTALS APPLIED TO DEBYE-WALLER FACTOR AND EQUATION OF STATE - HUNG, NGUYEN VAN (Communications in Physics, 2024)
Analytical expressions for the Morse potential parameters for fcc, bcc and hcp crystals have been developed. They contain the energy of sublimation, the compressibility and the lattice constant. Numerical results for Cu (fcc), W (bcc) and Zn (hcp) agree well with the measured values. Debye-Waller factors in X-ray absorption fine structure (XAFS) and equation of state computed using the obtained Morse potential parameters agree well with the experimental results